2022
DOI: 10.1371/journal.pntd.0009971
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal protozoan parasites among school children in africa: A systematic review and meta-analysis

Abstract: Introduction Parasitic infections, especially intestinal protozoan parasites (IPPs) remain a significant public health issue in Africa, where many conditions favour the transmission and children are the primary victims. This systematic review and meta-analysis was carried out with the objective of assessing the prevalence of IPPs among school children in Africa. Methods Relevant studies published between January 2000 and December 2020 were identified by systematic online search on PubMed, Web of Science, Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…Sensitivity analyses showed that the summary of the pooled estimates was unaffected significantly by the removal of outlier studies and moderate-quality studies (Supplementary file 2, Table 1 ). The prevalence rate stayed within the 95% CI for the relevant total prevalence [ 22 ]. Thus, we can conclude that the pooled estimated prevalence was validated by the reliability and rationality of our analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analyses showed that the summary of the pooled estimates was unaffected significantly by the removal of outlier studies and moderate-quality studies (Supplementary file 2, Table 1 ). The prevalence rate stayed within the 95% CI for the relevant total prevalence [ 22 ]. Thus, we can conclude that the pooled estimated prevalence was validated by the reliability and rationality of our analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical analysis was done applying the Jamovi software (keeping the significance level at <0.05), while the Galbraith plot and geographic distribution map were generated using RStudio. Additionally, sensitivity analysis was used to examine the robustness of the pooled estimate by removing studies with small sample sizes ( n ≤ 200), studies with intermediate quality that had moderate risk of bias rating score between 6 and 7, and studies with outliers [ 22 ]. The presence of outliers was determined via a z-score approach- a score of > ± 1.96 was termed as potential outlier (Supplementary file 2, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…and E. coli were most frequently diagnosed in June and September, respectively. Giardia and E. coli are enteric protozoans commonly detected in human fecal samples in Senegal and other African countries [ 16 , 17 ]. Giardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Each study was assessed on the basis of the proportion of ‘yes’ answers given to the items. The high proportion (≥70%) of ‘yes’ refers to high-quality study (low risk of bias), whilst the moderate (50–69%) and low proportion (≤49%) of ‘yes’ refer to moderate- and low-quality studies, respectively [ 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%